Helicenes: The Photochemical Ring-Closure of Polymer-Supported 1,2-Diarylethylenes: Hexahelicene- and benzo[c]phenanthrene-2-carbaldehyde - Jean-Marie Vanest; Mohamed Gorsane; Valery Libert; Jacques Pecher; Richard H. Martin (CHIMIA)
Photolysis of a suspension (C6H6;I2) of 1-(4-formylphenyl)-2-(2-benzo[c]phenanthryl)ethylene and 1-(4-formylphenyl)-2-(2-naphthyl)ethylene anchored on a styrene-divinylbenzene copolymer (1a and 1b), followed by hydrolysis, yielded hexahelicene-2-carbaldehyde (2a) and benzo[c]phenanthrene-2-carbaldehyde (2b) respectively. The photochemical ring-closure leading to 2b was also observed when the substituted polymer 1b was irradiated in the absence of a solvent.